APPROPRIATE CALIBRATION INTERVALS OF LABORATORY TEST EQUIPMENT IN ACCORDANCE WITH THE INTERNATIONAL IECEE REGULATIONS AND ITE PREDOM DIVISION ACTIVITY - Łysko, Jan; Starczewski, Marek; Walczak-Złotkowska, Joanna (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
Requirements for traceability of calibrations and calibration intervals contained in the document IECEE OD-5011 for the testing laboratories IECEE members are presented. Among the others, the issues related to selection of a calibration laboratory, calibration intervals for particular group of test equipment, requirements for traceability of calibrations as well as the matters of test equipment on the status of "Initial Calibration Only” were overviewed. Information about the IECEE OD-5011 application in the laboratory practice of ITE PREDOM Division is presented as well.